Optimize 2,4-D concentration and callus induction time enhance callus proliferation and plant regeneration of three rice genotypes (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Carsono N, Juwendah E, Liberty, Sari S, Damayanti F, Rachmadi M. 2021. Optimize 2,4-D concentration and callus induction time enhance callus proliferation and plant regeneration of three rice genotypes. Biodiversitas 22: 2555-2560. The development of callus in the course of transgenic rice avoids the somaclonal variants. To obtain a high number of normal phenotypes and a low number of somaclonal variants requires an appropriate 2,4-D concentration. In this study, we obtained the best callus induction time and a high number of green plant regeneration for three responsive rice genotypes on different 2,4-D concentrations in NB5 medium. The mature seeds of rice embryos were used as explants. A completely randomized factorial design was applied with four levels of 2,4-D concentrations (0, 1, 3, and 5 ppm), two levels of induction time (one and two weeks), and three rice genotypes (cv. Fatmawati, Nipponbare, and Kitaake). The study revealed that there was no interaction effect among genotype, 2,4-D concentration, and callus induction time. Three rice genotypes performed best in callus proliferation and regeneration. One-week callus induction time showed higher callus growth capacity (CGC) as compared to two-week callus induction time. Shoot regeneration capacity (SRC) was independently affected by genotype as well as by callus induction time. The interaction effect between 2,4-D concentration and callus induction time was observed on plant regeneration capacity (PRC). Without the addition of 2,4-D and 1 ppm of 2,4-D, the green plant regeneration capacity (GRC) was comparatively higher. Addition of 2,4-D showed a significant effect, especially at the plant regeneration stage. We found that one-week callus induction was the best treatment for callus proliferation and plant regeneration. We recommend the use of one-week callus induction and 1 ppm of 2,4-D for rice callus proliferation (sub-culture) and subsequent plant regeneration.
Keywords: in vitro culture, somaclonal variants, sub culture, rice.